The Neuropathy as an Adverse Effect of Chemotherapy Diminished After Administration of Dietary Supplement with Iron Citrate – Case Study - Kusnir, Patrik; Baig, Shahbaz (Futurity Medicine, 2024)
Aims: This research examined how adding iron citrate (Synthesit) affected chemotherapy-induced nerve damage in a patient diagnosed with primary fallopian tube cancer. Methodology: A 51-year-old Lithuanian woman received adjuvant chemotherapy and iron citrate. The blood indices and inflammation markers were monitored. Results: The patient showed macrocytic normochromic anemia, fluctuating platelet parameters, and varied procalcitonin levels, suggesting Synthesit influences immune function and hematologic parameters during chemotherapy. Scientific Novelty: This study distinctively investigated the influence of iron citrate on changes in hematologic and immune parameters during chemotherapy. Conclusion: Synthesit may affect the blood counts, red blood cell production, and immune markers, aiding in chemotherapy-induced neuropathy management.